Analysis of the effect of mutual inductance on reducing output current ripple of the modified DC-DC Cuk converter - Driantama, Nabil; Dahono, Andriazis; Rizqiawan, Arwindra; Furqani, Jihad (Institute of Advanced Engineering and Science, 2024)
DC-DC converters exhibiting minimal input and output ripple are extensively employed across a diverse range of applications. This paper presents a proposed modification to the DC-DC Cuk converter. The converter is developed by modifying a conventional Cuk DC-DC converter to exhibit boost characteristics. The DC-DC converters possess the capability to function as versatile units that can be employed in a multitude of applications, ranging from DC-DC conversion to DC-AC conversion (inversion). This paper presents a novel DC-DC converter design that aims to achieve reduced ripple in both input and output currents. By employing the principle of mutual inductance, it is possible to further mitigate the presence of ripple current. The analysis of the impact of mutual inductance on the output voltage and ripple current of the proposed converter has been conducted. The validity of the derived analytical method has been confirmed through both simulated and experimental investigations. The utilization of mutual inductance in the proposed modified Cuk converter has been demonstrated to result in reduced current ripple.